Ecotheological Dimensions of Roko Molas Poco in the Tradition of Making Traditional Houses of the Manggarai Community - NTT - Benny Denar; Sefrianus Juhani; Armada Riyanto (Journal of Asian Orientation in Theology, 2021)
This article aims to show and introduce ecotheological values of “roko molas poco” ritual in the tradition of making traditional houses of Manggarai people – west Flores – East Nusa Tenggara (NTT). The approach used in collecting information about these rituals is qualitative, using ethnographic method. The result of this research is that the “roko molas poco” ritual ini the tradition of making traditional houses of Manggarai people has very rich messages and ecothelogical values. These values can be used as important themes for inculturation of environmental theology in Manggarai people who are mostly Catholics and generally still adhere to their ancestors’ traditions and culture. These values can be used as important themes for inculturation of environmental theology in Manggarai people who are mostly Catholics and generally still adhere to the traditions and culture of their ancestors. It is believed that by strengthening ecotheological inculturation, ecological pastoral efforts in preventing a massive influx of ecological destruction can be easily carried out.